Peningkatan Kompetensi Pedagogik Calon Guru SD/MI Melalui Workshop Pengembangan Media Pembelajaran Interaktif berbasis Quizizz - Ibrahim; Ida Ermiana; Nurhasanah; Asiah Nikmah Rahmatih; Gita Prima Putra (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2026)
The advancement of digital technology requires teachers, including pre-service elementary school (SD/MI) teachers, to integrate interactive learning media into the teaching process. However, preliminary observations showed that most pre-service teachers had limited understanding of utilizing Quizizz, resulting in low pedagogical creativity and skills. To address this issue, an applicative and participatory workshop was conducted to enhance pedagogical competence, specifically technical mastery and creativity in developing Quizizz-based learning media, while providing direct hands-on technology integration experience. This activity utilized a Participatory Action Research (PAR) method emphasizing active student involvement. The subjects were 29 pre-service elementary teachers from the PGMI Study Program at UIN Mataram. Data were collected via pre-test and post-test questionnaires, observation sheets, and media product analysis, which were then evaluated using descriptive quantitative and qualitative approaches. The results revealed a significant improvement: before the workshop, most students only had basic knowledge (68.2% moderate, 18.2% no understanding), whereas post-workshop, 72.4% stated they had a very high understanding. Furthermore, 75.9% considered the workshop highly beneficial for designing interactive and innovative lessons. The resulting media products also showed remarkable improvements in design, interactivity, and content relevance. In conclusion, the Quizizz-based workshop effectively enhanced pedagogical competence for the digital era.